Crime and punishment in Oregon, 1875 - 1915: a study of four communities - Laythe, Joseph Willard (Edwin Mellen Press, 2008)
Introduction -- The rogues of river city -- Crime and punishment in Portland, Oregon, 1875-1915 -- The river city -- The settler's laws -- Tools to the city -- A city of anonymous victims -- The benefit of urban anonymity -- Asserting moral superiority -- Crime and punishment in Eugene, Oregon, 1897-1915 -- The satellite community -- Formal law and informal practices -- Offenses to the moral order -- Alternate measures -- Harlots, hanging, and hoolihaning -- Crime and punishment in Pendleton, Oregon, 1875-1915 -- In god forsaken country -- The haphazard law -- Wild, wooly, and tolerant -- Mixed messages -- Demimonde on the decline -- Crime and punishment in Jacksonville, Oregon, 1875-1915 -- A mining town of men the rough-hewn law -- Naughty neighbors and friends alike -- Punishment? -- Conclusion